2021
DOI: 10.2196/30624
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Emotional Expressiveness of a Female Digital Human on Loneliness, Stress, Perceived Support, and Closeness Across Genders: Randomized Controlled Trial

Abstract: Background Loneliness is a growing public health problem that has been exacerbated in vulnerable groups during the COVID-19 pandemic. Social support interventions have been shown to reduce loneliness, including when delivered through technology. Digital humans are a new type of computer agent that show promise as supportive peers in health care. For digital humans to be effective and engaging support persons, it is important that they develop closeness with people. Closeness can be increased by emo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…Participants commented positively when they felt the conversation flow/experience felt similar to a natural conversation. Participants' preference for emotionally expressive voice is confirmed by prior studies, for example Loveys et al (2021) who showed that emotional expressiveness in the voice resulted in increased feelings of caring (in female participants). Negative comments generally revolved around perceptions of an impersonal or robotic nature of the conversational agent, inappropriate pace of conversation (too slow or fast), too few conversational turns, and dislike of some interaction topics.…”
Section: Discussionmentioning
confidence: 96%
“…Participants commented positively when they felt the conversation flow/experience felt similar to a natural conversation. Participants' preference for emotionally expressive voice is confirmed by prior studies, for example Loveys et al (2021) who showed that emotional expressiveness in the voice resulted in increased feelings of caring (in female participants). Negative comments generally revolved around perceptions of an impersonal or robotic nature of the conversational agent, inappropriate pace of conversation (too slow or fast), too few conversational turns, and dislike of some interaction topics.…”
Section: Discussionmentioning
confidence: 96%
“…The on-off term could describe different performances that the units are involved in and characterize the tasks' nature, since each task requires a specific amount of attention (Castellanos et al, 2005 ; Ghorbanian et al, 2013 ; Katsuki and Constantinidis, 2013 ). The a AT and a PT parameters are related to the variability of the performance, since variability is counted as the attentional diversion indicator in various studies (Voss et al, 2004 ; Thissen et al, 2014 ; Loveys et al, 2021 ). Therefore, the value of a AT and a PT is estimated based on the scale of the variance of each task in different sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Abdollahi et al 19 designed a socially assistive robot with empathy, adopting a multimodal emotional recognition algorithm and emotional expression system to provide companionship for the elderly with depression and dementia. The second term “Closeness” refers to personal intimacy and emotional attachment 8 . Loveys et al 5 explored the emotional expression of virtual agents' faces and voices and presented that the presence of face and emotional voice help to establish positive relationships.…”
Section: Related Workmentioning
confidence: 99%
“…Virtual agents provide positive and catalytic effects on user engagement and immersion with their personalized, interactive, and diversified content. The media equation theory proposes that people respond to computers similarly to how they respond to real people 8 . Thus, humans are likely to interact and perceive virtual agents under the same paradigm.…”
Section: Introductionmentioning
confidence: 99%